Application of Unsere Straße Website in Learning German Listening Skill for Students Class XI IBB SMAN 1 Lawang - Nadia Nugraha; Sri Prameswari Indriwardhani (Universitas Negeri Malang, 2025)
Unsere Straße is a German learning website launched by Goethe Institute and KIDS Interactive GmbH. Unsere Straße contains interactive foto stories with audio and exercises level A1 with daily life theme that can be used to practice German listening skill. This research aims to describe the application of the website Unsere Straße in German listening skill for class XI IBB SMAN 1 Lawang and students’ responses of this website. The theme used was food and beverage. The research method used was descriptive method with a quantitative approach. The population of this study was the students of class XI IBB at SMAN 1 Lawang. The researcher collected data using questionnaire sheet. Results of the study show that the application website Unsere Straße took place interactively, conductively, and received positive responses from students. The Unsere Straße website provides audio-visual materials with native speakers and varied topics that can help train students' listening skill.